PENGEMBANGAN MEDIA HYPERLINK CANVA UNTUK MENINGKATKAN MINAT BELAJAR EKOLOGI DAN KEANEKARAGAMAN HAYATI - Ristanti, Aditya Putri; Surur, Agus Miftakus; Yusal, Yulianti; Mahmudah, Siti; Anggraini, Atika; Wulandari, Ratna Wahyu (Universitas Tanjungpura, 2025)
This study aims to develop a learning media based on canva hyperlinks to increase students' interest in learning the topics of Ecology and Biodiversity. The main problem faced is the lack of attractive and interactive learning media. This research uses the Research and Development (R&D) method with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study are seventh-grade students class VII-2 at MTsN 6 Nganjuk. Questionnaire data were analyzed quantitatively. The assessment results show that the interactive learning media based on canva hyperlinks is highly valid, with an average score of 87.14% by content experts and 100% by media experts. The practicality of the media is demonstrated by an 83% score from the student questionnaire, while the effectiveness test shows an increase in learning interest scores from 58% (low category) to 80% (moderate category), with an N-Gain value of 0.5 (moderate category). The Paired Sample T-Test results indicate a significance of 0.000 < 0.05, which shows a significant difference between pretest and posttest results of students